The ruling principles of pressed concrete mix compaction process and properties/Presuojamo betono mišinio savybių ir tankinimo proceso derinimo principai - Deltuva, Juozas; Rudžionis, Žymantas (Journal of Civil Engineering and Management, 1999)
The pressed products technology allows to automate production, to manufacture construction elements for finishing and grinding with precise dimensions, high strength, plain surface. But there are many unsolved problems in pressed products technology. The main of them are connected with the dependence of pressing pressure on concrete mix compaction level and its properties. The article deals with the mathematical description of pressed concrete mix properties when using concrete mix structural characteristics. The possibility was found to forecast pressed concrete mix needful pressure weight, density of product or relative deformation.Article in Lithuanian.First Published Online: 26 Jul 2012